Examining the impacts of grants on senior citizen beneficiaries in Kiboga District, Uganda. Issue 6 (18th August 2018) - Nalwanga, Rebecca; Lund, Ragnhild
ABSTRACT: This article presents the main findings of a study about the Senior Citizens Grant programme (SCG) piloted in Kiboga District, Uganda. Recognising elderly persons' vulnerabilities and acknowledging their capabilities is essential to motivate elderly beneficiaries of social grants towards self-sustenance rather than increasing dependency on such grants. Findings indicate that indigenous support systems, such as family members and agriculture directly influenced grant expenditure patterns and thus determined the well-being of grant beneficiaries. Old age vulnerability as the main criterion for eligibility and implementation casts shadows on older persons' capabilities needed to support their own lives, and hence impacts their well-being.